Processo de decisão de novos empreendimentos imobiliários para pequenas e médias empresas - Souza, André Soares de (2015)
The construction industry is characterized by the production by projects with long-term implementation, lack of flexibility after the start of construction, high output barrier, major commitment of financial resources and enterprises subject to inflationary pressures. Thus, the duration of the projects have a clear deadline to finish and the survival or propensity for self-perpetuation of these organizations depends on the renewal of this cycle. The overall objective of the study was to interpret the decision making process of new real estate projects in small and medium construction, focusing on the formalization of a model that represents this process as well as the understanding of its dynamics: the degree of structuring and formalization of each phase, the political aspects involved in decision making, the use of analytical or intuitive methodologies, participants of each stage, the reasons for participation and the type of influence that each actor adds to the process. It is a multicases and comparative study of four small and four companies of medium-sized construction building of the State of Espirito Santo. Data were collected through interviews with the founders of these companies and data analysis used analysis techniques of narrative content analysis and analysis of statistical correlation. As a result of the research was proposed a model of the new ventures decision process for small and medium enterprises, dynamic and flexible, consisting of six stages. The analyzes indicated that small companies make the decision process of new projects of less structured manner, with the power of centralized decision in owners partners based on experience and intuition to overlay analytical methodologies. As responsible for the growth of small businesses were identified inertial continued growth engines of innovation and related diversification.